Channel coding : theory, algorithms, and applications - Declerq, David; Fossorier, Marc, 1964-; Biglieri, Ezio (Academic Press library in mobile and wireless communications., 2014)
This book gives a review of the principles, methods and techniques of important and emerging research topics and technologies in Channel Coding, including theory, algorithms, and applications. Edited by leading people in the field who, through their reputation, have been able to commission experts to write on a particular topic. With this reference source you will: Quickly grasp a new area of research Understand the underlying principles of a topic and its applicationsAscertain how a topic relates to other areas and learn of the research issues yet to be resolvedQuick tutorial reviews o.